Karakteristik Sifat Fisiko-Kimia Mi Basah Subtitusi Tepung Sorgum (Sorghum bicolor L. Moench) Diperkaya Serat Rumput Laut (Gracilaria sp.) - Alifianti Nur Waqiah; Damat Damat; Desiana Nuriza Putri (Universitas Muhammadiyah Malang, 2019)
Noodles are consisting of main high protein flour. Data consumption of noodles in 2014 in Indonesia gain 2,2 million ton, this number was going high gradually in every next year. The substitute material which has similarities with what has been used in the last decade is sorghum starch. The aim of this study was to determine the effect of the composition of sorghum starch with seaweed pulp. The research method in is factorial Randomized Block Design (RBD). The first factor used was the difference in the ratio of wheat flour with sorghum starch which was added at 80:20; 60:40; 50:50 Factor II is the addition of seaweed which is 10%, 20%, and 30%. Quality starch noodles within analysis: water content, ash content, protein content, fat content, crude fiber content, and organoleptic (texture, taste, color, and aroma (smell)). The best results were obtained in the T1R1 treatment which got rank 1 with water content 33.38%, ash content 2.05%, protein content 8.31%, fiber content 12.92%, fat content 1.22%, organoleptic aroma 2.94 with aroma value